Kearifan Lokal dan Penerapannya di Sekolah - Harahap, Rahimul (MODELING: Jurnal Program Studi PGMI, 2023)
Local wisdom describes how to behave and act in response to changes that are unique to the local physical and cultural environment. Local potential in every region in Indonesia is a wealth of natural, human, technological and cultural resources that must be maintained and developed to promote a more civilized life. In general, learning in schools pays little attention to this local aspect, so that slowly the younger generation begins to leave the noble values of the local area. The purpose of this article is to describe the form of planting local wisdom through education or schools.